A description of a fetal syndrome associated with HNF1B mutation and a wide intrafamilial disease variability. Issue 12 (29th October 2013) - Rasmussen, Maria; Ramsing, Mette; Petersen, Olav Bjørn; Vogel, Ida; Sunde, Lone
Abstract : MODY5, renal cysts, and diabetes syndrome are autosomal dominant entities caused by mutation in the HNF1B gene. Here we report two fetal siblings and their father who have a HNF1B missense mutation and describe the fetal phenotype associated with mutation in this gene. To the best of our knowledge two non‐twin siblings with a missense mutation and a severe phenotype have not been reported previously. © 2013 Wiley Periodicals, Inc.